2020
DOI: 10.1101/2020.04.30.20085670
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Beyond the Spike: identification of viral targets of the antibody response to SARS-CoV-2 in COVID-19 patients

Abstract: 26 Background: The SARS-CoV-2 virus emerged in December 2019 and caused a 27 pandemic associated with a spectrum of COVID-19 disease ranging from 28 asymptomatic to lethal infection. Serology testing is important for diagnosis of 29 infection, determining infection attack rates and immunity in the population. It also 30 informs vaccine development. Although several serology tests are in use, improving 31 their specificity and sensitivity for early diagnosis on the one hand and for detecting 32 past infection f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 37 publications
0
59
1
1
Order By: Relevance
“…The presence of such antibodies has been interpreted as cross-reactivity with antigens of coronaviruses causing the common cold (10)(44) (45). Indeed, higher sequence homology at the protein level between SARS-CoV-2 and coronaviruses has been reported for N (particularly N-terminal and central regions), M and S2 (10)(46) (47). Pre-existing SARS-CoV-2-specific T cells have been recently reported and also attributed to cross-reactivity to human coronaviruses previously encountered (48) (49).…”
Section: Discussionmentioning
confidence: 98%
“…The presence of such antibodies has been interpreted as cross-reactivity with antigens of coronaviruses causing the common cold (10)(44) (45). Indeed, higher sequence homology at the protein level between SARS-CoV-2 and coronaviruses has been reported for N (particularly N-terminal and central regions), M and S2 (10)(46) (47). Pre-existing SARS-CoV-2-specific T cells have been recently reported and also attributed to cross-reactivity to human coronaviruses previously encountered (48) (49).…”
Section: Discussionmentioning
confidence: 98%
“…According to current data, S protein cross-reactive antibodies are not produced in the receptor-binding domain region. 46 Moreover, recent studies have found that N protein antibodies appear earlier than those of S protein, 47 which further suggests that early high-response antibodies are unlikely to provide protection against virus entry. Therefore, cross-protection is less likely to occur, but more research is needed to address this possibility.…”
Section: Limitations and Potential Solutionsmentioning
confidence: 99%
“…The antibody response generated following SARS-CoV-2 infection is diverse, consisting of multiple isotypes targeting several proteins on the virus surface including the spike protein (and its receptor binding domain) and the nucleoprotein [16]. This complexity of biomarkers provides both a challenge and an opportunity for diagnostics research.…”
Section: Introductionmentioning
confidence: 99%